2016
DOI: 10.3892/or.2016.5112
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic value of mitochondrial serine hydroxyl-methyltransferase 2 as a breast cancer biomarker

Abstract: Mitochondrial serine hydroxylmethyltransferase 2 (SHMT2) is a key enzyme in the serine/glycine synthesis pathway. SHMT2 has been implicated as a critical component for tumor cell survival. The aim of the present study was to evaluate the prognostic value and efficiency of SHMT2 as a biomarker in patients with breast cancer. Individual and pooled survival analyses were performed on five independent breast cancer microarray datasets. Gene signatures enriched by SHMT2 were also analyzed in these datasets. SHMT2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Similarly, many other mitochondria-resident APE1-PPIs were found to be commonly up-regulated in the analyzed datasets. Among these, it is worth mentioning: (i) SHMT2 (serine hydroxymethyltransferase), that mainly localizes to the matrix, nucleoid and inner membranes, and is known to be targeted by c-myc for cell survival, with various studies confirming its bad prognostic power in different cancer types [87][88][89][90][91] ; (ii) pro-apoptotic protein SLC25A6 (mitochondrial ADP/ATP carrier-3, AAC3) 92,93 ; (iii) ROS regulating respiratory complex III protein UQCRC2 (ubiquinol-cytochrome c reductase complex core protein 2) 94 ; (iv) respiratory complex II protein SDHB (succinate dehydrogenase B) 95 ; v) fatty acid βoxidation proteins ETFA (electron transfer flavoprotein subunit alpha) 96,97 and ACAA2 (acetyl-CoA acyltransferase 2) 98 ; vi) bad prognostic multifunctional LGALS3 (galectin-3) protein 99 ; (vii) autoimmunity protein HARS (histidyl-tRNA synthetase) 100 ; (viii) oxidative damage control protein IDH1 (isocitrate dehydrogenase 1) 101 . Additional matrix proteins were found being up-regulated in LIHC and LUAD, while down-regulated in PAAD; they included fatty acid β-oxidation proteins ECHS1 (enoyl coenzyme A hydratase short chain 1) 102 and ETFB (electron transfer flavoprotein subunit beta) 103 , multifunctional protein 17β-HSD10 (17β-hydroxysteroid dehydrogenase type 10, encoded by HSD17B10) 104 and mitochondrial protein processor PMPCA (mitochondrial-processing peptidase subunit alpha) 105 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many other mitochondria-resident APE1-PPIs were found to be commonly up-regulated in the analyzed datasets. Among these, it is worth mentioning: (i) SHMT2 (serine hydroxymethyltransferase), that mainly localizes to the matrix, nucleoid and inner membranes, and is known to be targeted by c-myc for cell survival, with various studies confirming its bad prognostic power in different cancer types [87][88][89][90][91] ; (ii) pro-apoptotic protein SLC25A6 (mitochondrial ADP/ATP carrier-3, AAC3) 92,93 ; (iii) ROS regulating respiratory complex III protein UQCRC2 (ubiquinol-cytochrome c reductase complex core protein 2) 94 ; (iv) respiratory complex II protein SDHB (succinate dehydrogenase B) 95 ; v) fatty acid βoxidation proteins ETFA (electron transfer flavoprotein subunit alpha) 96,97 and ACAA2 (acetyl-CoA acyltransferase 2) 98 ; vi) bad prognostic multifunctional LGALS3 (galectin-3) protein 99 ; (vii) autoimmunity protein HARS (histidyl-tRNA synthetase) 100 ; (viii) oxidative damage control protein IDH1 (isocitrate dehydrogenase 1) 101 . Additional matrix proteins were found being up-regulated in LIHC and LUAD, while down-regulated in PAAD; they included fatty acid β-oxidation proteins ECHS1 (enoyl coenzyme A hydratase short chain 1) 102 and ETFB (electron transfer flavoprotein subunit beta) 103 , multifunctional protein 17β-HSD10 (17β-hydroxysteroid dehydrogenase type 10, encoded by HSD17B10) 104 and mitochondrial protein processor PMPCA (mitochondrial-processing peptidase subunit alpha) 105 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 Accumulating studies have reported that abnormal expression of SHMT2 may play an important role in tumorigenesis and tumor progression of various human malignancies. 8 11 Especially, Kim et al 12 indicated that SHMT2 was elevated in a subset of glioma cells and promoted changes in metabolism that allowed cells to survive in an ischemic tumor microenvironment. However, its clinical relevance in human gliomas remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SHMT2 is a key enzyme in one-carbon metabolism, and is responsible for the conversion of serine to glycine. Several studies have found that SHMT2 is elevated in a range of tumors, and high levels of SHMT2 are associated with poor prognosis in patients [17,[28][29][30]. One study found that SHMT2 contributes to cancer cell survival in the harsh tumor microenvironment, which relies on glycine clearance [20].…”
Section: Discussionmentioning
confidence: 99%
“…As the hub of serine catabolism and single carbon metabolism, SHMT2 plays a regulatory role, in which small molecular metabolites control cell proliferation [16]. SHMT2 has been reported to be up-regulated in a variety of cancer types such as breast cancer, hepatocellular carcinoma, and lung cancer, and elevated SHMT2 is signi cantly associated with poor prognosis of patients [17][18][19]. In glioma cells, SHMT2 has been shown to contribute to cell proliferation in ischemic and hypoxia tumor microenvironments [20].…”
Section: Introductionmentioning
confidence: 99%